Fisher Equation and Modigliani-Cohn Hypothesis in the Financial Markets - Chytilova, Helena (European Scientific Journal, ESJ, 2022)
Fisher equation in its conventional form suggests that nominal interest rate is the sum of real interest rate and expected inflation and, as such, it has been utilized as a standard component in economic literature to predict the behavior of nominal and real interest rates or to analyze investment returns. Nevertheless, Fisher equation has its flaws well documented in the empirical literature. This paper focuses on enriching contemporary theoretical underpinnings by paying attention to Fisher´s illusory nature of nominal interest rate, revisiting original roots of Fisher equation, and contrasting them with modern conventional form of Fisher equation. Consequently, implications will be derived for the relevance of a particular form of Fisher equation. Another important contribution is the connection of Fisher’s equation with money illusion through Modigliani-Cohn hypothesis (1979). This phenomenon might be responsible for an imperfect adjustment of the interest rate to expected inflation, thereby leading to substantial implications in financial markets.